Effects of a Delphi consensus acupuncture treatment protocol on the levels of stress and vascular tone in women undergoing in-vitro fertilization: a randomized clinical trial protocol - Yan Zhang; Jennifer Phy; Chris Scott-Johnson; Sheila Garos; Jennie Orlando; Samuel Prien; Jaou-Chen Huang (BMC, 2017)
Abstract Background The variability of published acupuncture protocols for patients undergoing In-Vitro Fertilization (IVF) complicates the interpretation of data and hinders our understanding of acupuncture's impact. In 2012, an acupuncture treatment protocol developed by a Delphi consensus process was published to describe the parameters of best practice acupuncture for Assisted Reproductive Technology and future research. However, there has been no clinical trial utilizing this protocol to assess the effects of acupuncture. This study aims to ﻿a﻿sse﻿ss the implementation of Dephi consensus acupuncture protocol and to examine the impact of acupuncture on stress and uterine and ovarian blood flow among women between ages 21-42 years seeking IVF. Methods/Design This study is a one site prospective, two-arm randomized controlled non-blind clinical trial conducted in a medical school-affiliated fertility center . Participants will be randomized 1:1 into either the acupuncture group or the standard of care (no acupuncture) group using computer generated tables. Both groups will have 3 regular clinical visits as their standard IVF care during an approximately 2 to 3 weeks window. Women who are randomized into the acupuncture group would receive three sessions based on the Delphi consensus acupuncture protocol in addition to the standard care. The first treatment will be administered between days 6 to 8 of the stimulated IVF cycle. The second session will be performed on the day of embryo transfer at least 1 h prior to the transfer. The third session will be performed within 48 h post-embryo transfer. Participants will be followed for their pregnancy test and pregnancy outcome when applicable. The outcomes stress and blood flow will be measured by a validated perceived stress scale and vasoactive molecules, respectively. Discussion Although recruitment and scheduling could be challenging at times, the Delphi consensus acupuncture protocol was implemented as planned and well-accepted by the patients. Because of the time-specified sessions around patients' IVF cycle, it is highly recommended to have on-site study acupuncturist(s) to accommodate the schedule. Trial Registration ClinicalTrials NCT02591186 registered on October 7, 2015.